2002
DOI: 10.1097/00007890-200211150-00017
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and interferon-?? gene polymorphisms in the development of bronchiolitis obliterans syndrome after lung transplantation1

Abstract: The presence of high-expression polymorphisms at position -174 of the IL-6 gene and position +874 of the IFN-gamma gene significantly increases the risk for BOS development after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…For the IL-6 gene, the G allele in the promoter À174 G/C is associated with high production and earlier development of BOS in lung transplant recipients. 58 We have observed that the frequency of acute persistent lung allograft rejection was increased in patients having IL-10 GCC/ACC haplotype (intermediate phenotype) associated with IL-6 G/C haplotype. 33 In contrast to the lung transplant patients, kidney transplants with the G allele are associated with long-term allograft survival.…”
Section: Interleukinmentioning
confidence: 90%
See 1 more Smart Citation
“…For the IL-6 gene, the G allele in the promoter À174 G/C is associated with high production and earlier development of BOS in lung transplant recipients. 58 We have observed that the frequency of acute persistent lung allograft rejection was increased in patients having IL-10 GCC/ACC haplotype (intermediate phenotype) associated with IL-6 G/C haplotype. 33 In contrast to the lung transplant patients, kidney transplants with the G allele are associated with long-term allograft survival.…”
Section: Interleukinmentioning
confidence: 90%
“…46,72,73 However, IFN-g may play a role in driving the chronic rejection process which would explain the association observed between IFN-g genotype and the development of OB in adult lung transplant recipients. 58,74 Lung transplant recipients who are of the high producer IFN-g genotype may be less likely to develop posttransplant lymphoproliferative disorder (PTLD). 75 Since PTLD has a viral etiology, this finding may relate to the anti-viral function of IFN-g.…”
Section: Interleukinmentioning
confidence: 99%
“…In a rat model for chronic pancreatitis IL-6 tissue expression was able to be established (11). IL-6 gene polymorphism led to an increased number of chronic fibrotic lung diseases in transplanted patients (26). In addition, patients with peritoneal dialysis related chronic peritonitis exhibited increased levels of IL-6 in the peritoneal dialysate effluent (15).…”
Section: Oral Submucosis Fibrosis -(S) +(S) +(S)mentioning
confidence: 99%
“…Similarly, polymorphisms in IL-6 and IFN-g genes that regulate the production of these cytokines have been shown to correlate with the development of BOS after lung transplantation, consistent with a proinflammatory role for IL-6 in the pathogenesis of this disease. 77 The role of these genes in both early and late pulmonary complications of HSCT setting should be evaluated. Polymorphisms that increase the risk of cGVHD might also be expected to increase the incidence of BOS.…”
Section: Future Directionsmentioning
confidence: 99%